Person-environment fit theory in built environment: a scoping review - Zhehan Zhang; Wenda Zhang; Suihan Zhang; Yaxiao Chen; Xinpeng Wang; Yuri Fujii; Nobuaki Furuya (Journal of Asian Architecture and Building Engineering, 2025)
Person-Environment Fit (P-E Fit) theory is an important concept for studying the complex relationships between people and the environment and for explaining individual behaviors. Recent research regarding the built environment typically focuses on P-E Fit to achieve a harmonious relationship between people and their surroundings. However, comprehensive knowledge of this research topic is insufficient for practical applications and future developments. This paper adopts a scoping review method to summarize the bibliometric features and the core components (i.e. person, environment, fit, and outcomes) regarding P-E Fit theory in the context of built environments, and discusses several existing knowledge gaps: the narrow scope of the topics, the unclear mechanism, and the lack of proactive and dynamic views. Finally, a new P-E Fit model is developed, and its strengths for sustainable improvement of the built environment are discussed. This review deepens the understanding of the literature, refines the theoretical framework, and provides researchers, designers, and policymakers with tools for developing research programs and practices for providing people-centered built environments from a P-E Fit perspective.